2018
DOI: 10.1186/s12879-018-3616-5
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis complicated with Guillain Barre syndrome, papillitis and thrombotic thrombocytopenic Purpura; a case report

Abstract: BackgroundLeptospirosis is a zoonosis commonly prevalent in tropical countries. Clinical course of leptospirosis varies from mild to severe disease. Here we present a case of leptospirosis complicated with Guillain-Barre Syndrome (GBS), papillitis, and Thrombotic Thrombocytopenic Purpura(TTP).Case presentationA 21-year-old Asian male presented with fever, myalgia, oliguria and dyspnoea where he was managed as for leptospirosis complicated with pulmonary haemorrhages and acute renal failure. Leptospirosis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…GBS has also been reported with posterior reversible encephalopathy syndrome (PRES), Covid-19 infections, myasthenia gravis, nephrotic syndrome, pulmonary tuberculosis to name a few [ [21] , [22] , [23] , [24] , [25] ]. However, as per our review we found only one case reporting “leptospirosis complicated by sequential GBS, papillitis and TTP [ 26 ]. We are reporting the second case but the first one concurrently affected by GBS and TTP.…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBS has also been reported with posterior reversible encephalopathy syndrome (PRES), Covid-19 infections, myasthenia gravis, nephrotic syndrome, pulmonary tuberculosis to name a few [ [21] , [22] , [23] , [24] , [25] ]. However, as per our review we found only one case reporting “leptospirosis complicated by sequential GBS, papillitis and TTP [ 26 ]. We are reporting the second case but the first one concurrently affected by GBS and TTP.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Campylobacter has been reported with TTP and GBS both [ 16 , 17 , [26] , [27] ]. Occurrence of GBS is sometimes 77 times higher in those who had Campylobacter infection compared to the general population [ 28 ].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…The pathogenic mechanism has been discussed for more than a century. The disease can be induced by a number of microorganisms, including Campylobacter jejuni , cytomegalovirus, leptospirosis, Epstein–Barr virus, Hepatitis E virus, and Zika virus ( Creange, 2016 ; Willison et al, 2016 ; Kobawaka Gamage and Fernando, 2018 ). Molecular mimicry of gangliosides caused by these pathogenic microorganisms may take part in the occurrence and development of GBS ( Goodfellow and Willison, 2016 ; Willison et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Varios tipos de infecciones han sido asociadas al SGB, principalmente de tipo respiratorio y gastrointestinal en 70% de los casos. La asociación con leptospirosis una de las zoonosis de mayor distribución mundial generada por la espiroqueta del orden Spirochaetales, de la familia Leptospiraceae, del género Leptospira se ha documentado con menor frecuencia (4)(5)(6)(7). Esta infección en la mayoría de los casos tiene una presentación clínica bifásica que co-mienza con un fase septicémica, seguida de manifestaciones inmunes con un espectro clínico amplio que va desde un síndrome febril con síntomas constitucionales leves hasta un cuadro severo acompañado de falla multiorgánica (8).…”
Section: Introductionunclassified